2015
DOI: 10.1902/jop.2015.140540
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Expression in Individuals With Chronic and Aggressive Periodontitis

Abstract: High expression of hTERT might be associated with periodontal disease progression, suggesting that hTERT could be a potential prognostic marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…146 Also, increased expression of the human telomerase reverse transcription (hTERT) enzyme has been noticed in patients with periodontitis. 147,148 Carcinogenesis is a multi-step process. Genetic alterations and different signaling pathways result in cell proliferation, resistance to apoptosis, invasion and metastasis.…”
Section: Genetic Alterations and The Risk Of Periodontitis Development And Carcinogenesismentioning
confidence: 99%
“…146 Also, increased expression of the human telomerase reverse transcription (hTERT) enzyme has been noticed in patients with periodontitis. 147,148 Carcinogenesis is a multi-step process. Genetic alterations and different signaling pathways result in cell proliferation, resistance to apoptosis, invasion and metastasis.…”
Section: Genetic Alterations and The Risk Of Periodontitis Development And Carcinogenesismentioning
confidence: 99%
“…Periodontal diseases have also been involved in the elevated risk of the cancer occurrence by overexpression of the human telomerase reverse transcription (hTERT) enzyme that was identified in patients with periodontitis. This result strongly suggests that both periodontitis and cancer are linked in disease-oriented pathways to progress to cellular differentiation and immortality (Refs 52,53).…”
Section: Extra-oral Cancermentioning
confidence: 86%
“…15,16 In the same way, aerodigestive cancer mortality has been shown to be elevated according to the severity of periodontitis. 17 Additionally, periodontal disease was demonstrated that the probability of having an oral leukoplakia experience grows in a dose-dependent manner, directly proportional to the gravity of periodontitis. Likewise, association with gingival inflammation, measured by bleeding on probing scores, was identified in patients with leukoplakia.…”
Section: Dear Editormentioning
confidence: 99%